Issues and concerns in verbal and graphic communication between various furniture companies and its clients - La'o, Pauline Angela C. (UP College of Home Economics, 2012)
Graphic and verbal communication, which includes written and oral communication, are essential elements in a successful business deal in the furniture manufacturing industry. However, not everyone is articulate and fluent in a language adept to the client. Hence, this study was formulated to determine the preferred graphic and verbal communication tools of furniture manufacturing companies. It aimed to explore the different issues and concerns involving graphic and verbal communication, and to suggest possible ways to address these. The study employed a descriptive research design, using purposive non-probability sampling in selecting 10 respondents from 5 furniture companes that have showrooms in LRI Design Plaza, Makati City. The respondents, having a minimum of 1-year work experience in dealing with clients, were interviewed and observed to gather data for this study. The results of this study show that e-mails emerged as the most preferred written communication tool in dealing with clients, with letters as the least preferred. In addition, personal meetings were considered the most preferred form of oral communication, while voicemails were the least preferred. However, data regarding the preference in presenting graphic communication tools were inconclusive because a majority was not reached. Issues about language barrier and mispronunciation emerged during data gathering, while productive-delivery schedule, verbal aptitude and graphic proficiency were the concerns brought up by the respondents. In consideration of these issues and concerns, proper training for the growth and success of the employees and the company is recommended. The furniture-manufacturing companies should review the capabilities of their employees to suit the requirements of their clients to improve and address the issues and concerns raised by the respondents in this study.